Pengaruh Gaya Kepemimpinan, Motivasi, dan Disiplin Kerja terhadap Kinerja Karyawan PT CJ Feed and Care Semarang Plant Cabang Batang - Dina Ulayya Aziizah; Muarifudin Muarifudin; Luthfi Arie Widzayanto (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study investigates the effects of leadership style, work motivation, and work discipline on employee performance in a manufacturing context. A quantitative survey was conducted among 66 employees in the packing department of PT CJ Feed and Care Semarang Plant, Batang Branch, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that leadership style and work discipline significantly enhance employee performance, whereas work motivation does not exhibit a significant effect. The model explains 54% of the variance in employee performance. These findings suggest that managerial control and leadership practices play a more decisive role than motivational factors in operational settings, where motivation may function primarily as a hygiene factor rather than a performance driver. The study contributes to the ongoing debate on the contextual nature of leadership, discipline, and motivation in employee performance research.